Pengaruh Citra Merek, Desain Kemasan, dan Promosi Terhadap Minat Beli Produk Rokok Surya Gudang Garam. Study Pada Masyarakat Surabaya Raya - Sadilah, Ainun; Febriansah, Rizky Eka; Indayani, Lilik (Universitas Islam Kadiri, 2025)
Abstract. In the cigarette industry in Indonesia, especially in Surabaya, Surya Gudang Garam products have become one of the brands that are in demand by the public. However, increasingly tight market competition and external challenges such as increased excise and the increasing popularity of electronic cigarettes (vapes) have affected the dynamics of cigarette product consumption. In addition, anti-smoking campaigns from the government and health organizations are getting stronger, creating pressure on this industry. In the midst of these conditions, marketing strategies become crucial factors in maintaining consumer purchasing interest. Brand image, packaging design, and promotion play an important role in attracting consumers, including non-smokers, by building a positive perception of the product. Therefore, this study aims to analyze how these three variables influence the purchasing interest of Surya Gudang Garam products in the Greater Surabaya community, as an effort to understand the effectiveness of marketing strategies in facing the current challenges of the cigarette industry. The population in this study includes residents of Greater Surabaya, with samples focused on non-smokers, in order to examine their interest in cigarette products through brand image, packaging design, and promotion factors. The research method used is non-probability sampling with a purposive sampling technique, and the number of respondents in this study was 100 people. After the data was collected, the data was processed using the SPSS 25 analysis program, with the analysis technique used being multiple linear regression. The results of the study indicate that Brand Image influences the Purchase Interest of Surya Gudang Garam Cigarette Products in the Greater Surabaya Community. Packaging Design influences the Purchase Interest of Surya Gudang Garam Cigarette Products in the Greater Surabaya Community. Promotion influences the Purchase Interest of Surya Gudang Garam Cigarette Products in the Greater Surabaya Community